2021
DOI: 10.3389/fmolb.2021.684622
|View full text |Cite
|
Sign up to set email alerts
|

Crowding Effects on the Structure and Dynamics of the Intrinsically Disordered Nuclear Chromatin Protein NUPR1

Abstract: The intracellular environment is crowded with macromolecules, including sugars, proteins and nucleic acids. In the cytoplasm, crowding effects are capable of excluding up to 40% of the volume available to any macromolecule when compared to dilute conditions. NUPR1 is an intrinsically disordered protein (IDP) involved in cell-cycle regulation, stress-cell response, apoptosis processes, DNA binding and repair, chromatin remodeling and transcription. Simulations of molecular crowding predict that IDPs can adopt c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 71 publications
(109 reference statements)
0
18
0
Order By: Relevance
“…Nowadays, three main families of spin labels are routinely used for in vitro studies (Fig. 2): nitroxyl radical derivatives (Nitroxides [1][2][3]), metals (Gd(III); Cu(II); Mn(II) chelated by high-affinity cages [4] or protein residues like histideines [5]), triarylmethyl radicals (trityl, OX-SLIM [6]). Reviews on the advantages and limits of these spin labels can be found in the literature.…”
Section: Toward In-cell Sdsl-epr Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nowadays, three main families of spin labels are routinely used for in vitro studies (Fig. 2): nitroxyl radical derivatives (Nitroxides [1][2][3]), metals (Gd(III); Cu(II); Mn(II) chelated by high-affinity cages [4] or protein residues like histideines [5]), triarylmethyl radicals (trityl, OX-SLIM [6]). Reviews on the advantages and limits of these spin labels can be found in the literature.…”
Section: Toward In-cell Sdsl-epr Experimentsmentioning
confidence: 99%
“…The first works on local spin-label dynamics appeared between 1989 and 1996. 1–5 From that time on, this approach has been successfully used to study folding-unfolding-aggregation events, 6–8 intermolecular regulations, 9,10 bio-condensates and coacervates, 11–13 changes in solvent accessibility, 14–16 and interaction between biomolecules. 17,18…”
Section: Studying Biomolecules By Sdsl–epr: From In Vitro To In-cell ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Although X-ray crystallography and cryo-electron microscopy may both be able to trap more than one protein conformer of globular proteins, solution techniques are undoubtedly preferred for uncovering the dynamics of flexible proteins, with NMR being the approach that initially highlighted these features in proteins using different types of measurements (chemical shifts, R1, R2, J-couplings, NOEs, and RDCs). Lately, there have also been efforts dedicated to studying the dynamics of flexible and intrinsically disordered proteins (IDPs) in the cellular context using in-cell NMR and EPR spectroscopy, as a protein’s conformational behavior may differ from what is observed in isolation in the test tube ( Gerez, Prymaczok, and Riek, 2020 ; Bonucci et al, 2021 ). However, due to various experimental challenges, these methods have not become widely used in the community of structural biology.…”
Section: Introductionmentioning
confidence: 99%
“…These molecules self-assemble into micelle nanocarriers for the encapsulation of chemotherapeutics or other drugs [ 27 ], and they may exhibit a pH-induced phase transition from a low-dispersity spherical shape to an elongated worm-like one [ 26 ], representing a potential mechanism for the hold-and-release of cargoes. In fact, IDP-based constructs have unique properties of responsiveness towards pH, temperature, and molecular crowding conditions [ 28 ], which are key factors in the microenvironment of diseased tissues. IDP regions can also form nanocages [ 29 ] or be attached to the surface of conjugated nanoparticles [ 30 ], therefore constituting a stealth layer to modulate their circulation half-life.…”
mentioning
confidence: 99%